Dementia Pugilistica with clinical features of Alzheimer's disease Dementia pugilistica com características clínicas de doença de Alzheimer - Renata Areza-Fegyveres; Sergio Rosemberg; Rosa Maria R.P.S. Castro; Claudia Sellitto Porto; Valéria Santoro Bahia; Paulo Caramelli; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
A 61-year-old ex-boxer presented with a three-year history of progressive memory decline. During a seven-year follow-up period, there was a continuous cognitive decline, very similar to that usually observed in Alzheimer's disease. Parkinsonian, pyramidal or cerebellar signs were conspicuously absent. Neuropathological examination revealed the typical features of dementia pugilistica: cavum septi pellucidi with multiple fenestrations, numerous neurofibrillary tangles in the cerebral isocortex and hippocampus (and rare senile plaques). Immunohistochemistry disclosed a high number of tau protein deposits and scarce beta-amyloid staining. This case shows that dementia pugilistica may present with clinical features practically undistinguishable from Alzheimer's disease. Um ex-boxeador de 61 anos apresentou-se com história de três anos de perda progressiva de memória e evoluiu com declínio cognitivo lentamente progressivo, sugestivo de doença de Alzheimer, durante seguimento de sete anos. Sinais parkinsonianos, piramidais ou cerebelares estiveram ausentes durante toda a evolução. Exame neuropatológico evidenciou características típicas de dementia pugilistica: cavum do septo pelúcido com múltiplas fenestrações, numerosos emaranhados neurofibrilares no isocórtex cerebral e hipocampo (e raras placas senis). Imuno-histoquímica confirmou número elevado de depósitos de proteína tau e raros de beta-amilóide. Este caso demonstra que dementia pugilistica pode apresentar quadro clínico indistinguível daquele da doença de Alzheimer.